Pengaruh Konseling Gizi Pada Asupan Makan Remaja Obesitas Di Smp Kristen Woloan Kota Tomohon - Henry S. Imbar; Jufri Sineke; Candra Rugian (Jurnal GIZIDO, 2019)
Feeding intake is all types of food and beverages consumed by the human body food is also one of the very basic human needs because it affects the existence and survival of human today. This study aims to determine the effect of nutritional counseling on the intake of eating obese adolescents and to know the intake of food before and after counseling in SMP Kristen Woloan Tomohon.This type of research is a type of pre-experimental study with a pre-test design of one gramoup design. The number of samples used in this study were 20 respondents. Feed intake data was taken by first measuring the treatment in the study gramoup (pre-test) with a 24-hour recall method carried out 3 days, and providing nutritional counseling, and measured again after being given nutritional counseling treatment (post test) with a 3-day recall method . Data analysis using wilcoxon analysis From the results showed that energy intake, protein intake, fat intake, and carbohydrate intake experienced penuruna after being given counseling. Based on the results of statistical analysis using wilcoxon test ρ =0.000 (<0.05) which means there is influence counseling on feeding intake of adolescent obesity. Conclusion There is the influence of nutritional counseling on the intake of eating obese adolescents